Devising a method for assessing efficiency of the cooling system and determining the thermal state of vertical synchronous hydrogenerators using three-dimensional CFD simulation - Yehorov, Andrii; Kravchenko, Stanislav; Duniev, Oleksii; Vasyliev, Oleksandr; Hromenko, Denys; Lukashevych, Serhii; Buhaiov, Oleh; Liakhov, Kostiantyn; Kovryga, Anton; Obidin, Dmytro (Eastern-European Journal of Enterprise Technologies, 2026)
This study explores heat and mass transfer processes in the structural elements of an umbrella-type hydrogenerator, as well as the ventilation and cooling system in the active components of the hydrogenerator. A vertical synchronous air-cooled hydrogenerator with a rated capacity of 60 MW has been investigated. The task addressed relates to the cooling efficiency of generator components. Conventional analytical calculation methods do not make it possible to identify local overheating zones and pressure distribution in complex ventilation channels. Therefore, it becomes necessary to use numerical methods and algorithms to calculate and analyze the cooling efficiency of the generator’s active parts. The main result of this study is the designed structure of the guide channels (blades) of the rotor, which provides the required air flow rate of 45 m3/s. At the same time, the maximum values of the winding temperature do not exceed the permissible values for class F insulation. The CFD calculation detailed the action of the superchargers and showed the real pressure in the channels and the volume of air passing through each section of the generator. The error between the results from CFD modeling and analytical calculations is less than 3%. The results are attributed to the detailed reproduction of the geometry of the ventilation channels in the 3D model, which made it possible to determine the real aerodynamic resistance and cooling medium consumption. The proposed method uses the boundary conditions of the third kind for a comprehensive calculation of the conjugate heat and mass transfer. The proposed structure could be implemented in the design and modernization of air-cooled hydrogenerators.